2020
DOI: 10.1088/1742-6596/1554/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Research of Mathematics Learning Device Development Based on Realistic Mathematics Education (RME)

Abstract: Based on the preliminary research stage conducted in Public Junior High School (SMPN) 3 Muara Bungo, it is obtained that students’ reasoning ability is low and has yet achieved optimum result. This is due to inappropriate learning device available in which it is yet facilitating the students in improving their mathematics reasoning. Therefore, it is of vital importance to develop learning devices in the form of lesson plan (RPP) and student worksheet (LKPD) based on Realistic Mathematics Education (RME). RME p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…It is shown by the results of his research that students with high logical-mathematical intelligence have a more systematic, logical problem-solving profile, and can explain completely. In line with this, (Ulfah et al, 2020) revealed that in mathematical logical intelligence there are steps or phases in solving problems, where the steps in solving the problem are systematic and logical steps. Starting from the stage of understanding the problem, planning a solution, carrying out the plan, and re-checking (Zayyadi, et al, 2019).…”
Section: Subject's Mathematical Logical Intelligencementioning
confidence: 87%
“…It is shown by the results of his research that students with high logical-mathematical intelligence have a more systematic, logical problem-solving profile, and can explain completely. In line with this, (Ulfah et al, 2020) revealed that in mathematical logical intelligence there are steps or phases in solving problems, where the steps in solving the problem are systematic and logical steps. Starting from the stage of understanding the problem, planning a solution, carrying out the plan, and re-checking (Zayyadi, et al, 2019).…”
Section: Subject's Mathematical Logical Intelligencementioning
confidence: 87%
“…The Mann-Whitney test is used for data that are not normally distributed, and the independent sample t-test is used for data that are normally distributed, for descriptive and inferential statistical testing. The steps involved in data processing are listed below in detail; First, using the normalized gain to determine the extent of the improvement in conceptual understanding and the development of students' self-determination (Ulfah et al, 2020;Noviani et al, 2017). The normalized gain can be determined using the following formula.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers determine the development model to be applied, namely the plomp development model. Plomp has three stages including preliminary research, development or prototyping phase and assessment phase [29]. Researchers limit the research to be carried out to the development or prototyping phase [30].…”
Section: Methodsmentioning
confidence: 99%